Otizmli Kardeşe Sahip Çocukların Yapısal Aile Terapisi Bağlamında Değerlendirilmesi. - YILMAZ, Mehmet; ATALAR, Uğur (Itobiad: Journal of the Human & Social Science Researches / İnsan ve Toplum Bilimleri Araştırmaları Dergisi, 2021)
Autism, which is a developmental disorder that has increased rapidly after the 1970s, is a disorder whose incidence has increased in recent years, and this increase also points to the increase in the number of children with autistic siblings. Autism, by its nature, requires more attention, time and resources for diagnosed individuals than children with normal development. For this reason, the stress caused by this situation can be a factor in the family. Structural family therapy developed by Minuchin in the 1960s suggests that family problems can be overcome by examining family interaction patterns and creating changes in family structure and organization. Structural family therapy approach considers the family as the basic system and argues that there are sub-systems of the family system. For example, each family has subsystems such as a parent subsystem, spouse subsystem, sibling subsystem, and kinship subsystem. According to the approach, which is a product of the system approach, subsystems have their own limits. According to this approach, which is known as the structural functional approach or functionalism in sociology, each subsystem operates within its own borders and supports the other. Thus, the family system continues to function. In this study, the answers given by the researchers to open-ended questions prepared by the researchers and conducted with 44 parents via Google Forms with families diagnosed with autism were analyzed in the context of structural family therapy. The research was planned in a qualitative design. According to the findings of the study, children with siblings with autism are included in the parent, sibling subsystem, and may experience social and behavioral problems depending on the boundaries between parents As a result of the analysis, demograms were created through the family systems mapping created by Salvador Minuchin. In the it was found that the structural boundaries and frames between parent-child-autistic sibling could not be maintained, and children with siblings with autism sometimes had to assume the role of parents. In this context, discussions were made and suggestions were made about how to deal with the problematic parts of family relationships of children with siblings with autism and their parents and to solve the problems.